The use of innovative and efficient nanocomposite (magnetic graphene oxide) for the reduction on of Fusarium mycotoxins in palm kernel cake - Pirouz, A. A.; Selamat, J.; Iqbal, S. Z.; Mirhosseini, H.; Karjiban, R. Abedi; Bakar, F. Abu (Nature Publishing Group, 2017)
Adsorption plays an important role in the removal of mycotoxins from feedstuffs. The main objective of this study was to investigate the efficacy of using magnetic graphene oxide nanocomposites (MGO) as an adsorbent for the reduction of Fusarium mycotoxins in naturally contaminated palm kernel cake (PKC). Liquid chromatography-tandem mass spectrometry (LC-MS/MS) was used to assess the mycotoxins in animal feed. Target mycotoxins included the zearalenone (ZEA), the fumonisins (FB1 and FB2) and trichothecenes (deoxynivalenol (DON), HT-2 and T-2 toxin). Response surface methodology (RSM) was applied to investigate the effects of time (3–7 h), temperature (30–50 °C) and pH (3–7) on the reduction. The response surface models with (R² = 0.94–0.99) were significantly fitted to predict mycotoxins in contaminated PKC. Furthermore, the method ensured a satisfactory adjustment of the polynomial regression models with the experimental data except for fumonisin B1 and B2, which decrease the adsorption of magnetic graphene oxide (MGO). The optimum reduction was performed at pH 6.2 for 5.2 h at of 40.6 °C. Under these optimum conditions, reduced levels of 69.57, 67.28, 57.40 and 37.17%, were achieved for DON, ZEA, HT-2, and T-2, respectively.